1997
DOI: 10.1039/a703716c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of dinuclear copper(II) complexes with a N6 pyridazine-derived ligand *

Abstract: A new hexadentate ligand 3,6-bis[(6-methyl-2-pyridyl)(2-pyridyl)methyl]pyridazine (mbdpdz) was prepared by a condensation reaction of 3,6-dichloropyridazine and (6-methyl-2-pyridyl)(2-pyridyl)methyllithium, and the following binuclear copper() complexes were obtained: [Cu 2 (mbdpdz)Cl 4 ] 1, [Cu 2 (mbdpdz)Br 4 ] 2, [Cu 2 (mbdpdz)-Cl 2 (OH)]Cl 3 and [Cu 2 (mbdpdz)Br 2 (OH)]Br 4. The crystal and molecular structures of the two isomorphous complexes 3 and 4 are reported. Both complexes crystallize in the monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Ligands based on a pyridazine core were first reported in 1993 and 1997, namely compounds 19a and 19b, from reaction of 3,6-dichloropyridazine with di-(2-pyridyl)methyllithium or (6-methyl-2-pyridyl)(2-pyridyl)methyllithium, respectively. [45,49] Manzur and co-workers studied the magnetism of binuclear copper(II) complexes with 19b, which present six-membered chelate rings around the metal centres; in these complexes the copper centres are bridged by both the diazine ligand and hydroxide, leading to quite short metal-metal distances. [49] In an earlier report, copper(II) chloride and bromide complexes were described in which two chloride or two bromide anions bridge the copper centres supported by coordination to 19a.…”
Section: Ditopic Ligands With Heteroarene Coresmentioning
confidence: 99%
See 1 more Smart Citation
“…Ligands based on a pyridazine core were first reported in 1993 and 1997, namely compounds 19a and 19b, from reaction of 3,6-dichloropyridazine with di-(2-pyridyl)methyllithium or (6-methyl-2-pyridyl)(2-pyridyl)methyllithium, respectively. [45,49] Manzur and co-workers studied the magnetism of binuclear copper(II) complexes with 19b, which present six-membered chelate rings around the metal centres; in these complexes the copper centres are bridged by both the diazine ligand and hydroxide, leading to quite short metal-metal distances. [49] In an earlier report, copper(II) chloride and bromide complexes were described in which two chloride or two bromide anions bridge the copper centres supported by coordination to 19a.…”
Section: Ditopic Ligands With Heteroarene Coresmentioning
confidence: 99%
“…[45,49] Manzur and co-workers studied the magnetism of binuclear copper(II) complexes with 19b, which present six-membered chelate rings around the metal centres; in these complexes the copper centres are bridged by both the diazine ligand and hydroxide, leading to quite short metal-metal distances. [49] In an earlier report, copper(II) chloride and bromide complexes were described in which two chloride or two bromide anions bridge the copper centres supported by coordination to 19a. [45] The authors concluded that 19a is not a particularly efficient bridge for facilitating magnetic interaction through the N-N diazine bridge, when it acts as a hexadentate ligand generating octahedral species and that the efficiency is even lower when the ligand is pentadentate and does not bond through both N-N atoms.…”
Section: Ditopic Ligands With Heteroarene Coresmentioning
confidence: 99%
“…between the corresponding singly-occupied molecular orbitals (so-called SOMOs), determines the type of coupling -ferromagnetic when the ground electronic state corresponds to the high-spin configuration with parallel orientation of electronic spins and antiferromagnetic when the ground electronic state is characterized by the low total spin with antiparallel orientation of the electronic spins [1,2]. Nowadays, the most prevalent and well studied organometallic magnetic systems are dinuclear copper(II) complexes with different types of linkers between the ligand-coordinated magnetic centers (-Hal-, [6,7], -OH-, [4,6,8,9] -OR-, [10][11][12][13] CN-, [14] -N^N-, [8,9,15] -N^O- [16,17] etc.). These complexes can demonstrate a variety of coupling types from strongly antiferomagnetic (exchange coupling constant J CuCu is strongly negative up to -1000 cm -1 ) [4][5][6] to moderately ferromagnetic (J CuCu is positive, typically of order 100 cm -1 ) [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although a wide range of the 2J values (À35 to À1304 cm À1 ) is found for mixed l-diazine with l-OH or l-halogeno bridging dinuclear copper(II) complexes [30][31][32][33], most of them show a strong anti-ferromagnetic interaction through the l-azine-bridge. A weak anti-ferromagnetic coupling (2J = À10.3 cm À1 ) was observed for a diazine-bridged dinuclear copper(II) complex [34].…”
Section: Magnetic Propertiesmentioning
confidence: 99%